'Medieval', 'Renaissance', 'modern'. Issues of periodization in Italian university history. Issue 4 (11th September 2013) - Denley, Peter
Abstract : Italian university historiography is strongly influenced by current notions of periodization and change. 'Medieval' universities have been seen as unique but soon outdated creations, to be overtaken by 'Renaissance' universities in which the driving forces were the requirements of 'princes' or whoever else was at the helm of the 'territorial state'. The 'Renaissance' universities, and even more their 'modern' successors, are supposed to have been more functional, more responsive to demand and to the aspirations of rulers and elites – and thus, by implication, more 'efficient'. But this reading fails to take full cognisance of the true significance of the medieval universities, which in practice were strongly pragmatic foundations as well as idealistic ones. From the thirteenth century, Italian universities in particular were locked in a mechanism of market forces that ensured that they were constantly open to fresh initiatives and constantly subject to change. This contribution reassesses these institutions and contests the traditional chronological perspectives.